Update on Rheumatic Heart Disease in Kano - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Rheumatic heart disease (RHD) remains a major public health problem in developing countries. Anecdotal reports across Africa show that the disease is coming less prevalent in the cities and the patients are surviving longer, although with a lot of morbidity. Between 2002 and 2006, 9.8% of 1312 patients were found to have RHD from our echocardiographic registry, with a mean age of 24 years. Therefore, we set out to review our current data for RHD to see if there are any changes in patterns of presentation in our center.Materials and Methods:This is a retrospective analysis of a prospectively collected echocardiography data between August 2010 and July 2012. The study was conducted at the Aminu Kano Teaching Hospital, Kano Nigeria. The procedure was performed with Aloka SSD 4000. The standard techniques for depicting the anatomical structures of the heart were employed. All echocardiographic procedures were performed by a cardiologist. Information obtained from the records included the age, gender, clinical diagnoses, and echocardiographic diagnoses. Prevalence and patterns were compared with previous findings.Results:During this period, a total of 1496 echocardiographic examinations were done. One hundred and four (7.0%) had RHD. There were 69 females (66.3%) and 35 males (33.7%) aged 30.7 + 14.0 years (range 12–70 years). Forty (38.5%) were aged 15–24 years. The commonest lesions were mixed mitral valve disease and aortic regurgitation (26.9%) followed by combination of mitral and aortic regurgitation (25%), and pure mitral regurgitation in 17.3%. Complications of RHD observed included secondary pulmonary hypertension (50%), left ventricular dysfunction (40.4%), atrial fibrillation (AF) (8.7%), infective endocarditis (1.9%), and intra cardiac thrombus (1.9%).Conclusion:RHD is still an important cause of cardiac morbidity. Although there is a reduction in prevalence compared to previous finding in the same center, while the patients are a bit older, they had more severe disease and still had complications at diagnosis.